2017
DOI: 10.1002/ijop.12471
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of Indian Affective Picture Database

Abstract: Since culturally salient stimuli for emotion recognition are scarce in India, we developed and validated a set of 140 coloured pictures of six basic emotions along with a neutral expression. The expressions were posed by four expressers, two males and two females, with mean age of 25.25 (SD 3.77) years. The expressions were captured from five different angles keeping the background uniform. These pictures were shown to 350 undergraduates who labelled the emotion and rated their intensity. The mean biased hit r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…This is supported by the N400 effect observed in the ERF analysis and the absence of significant decoding latency in the MVPA analysis. Both the studies (Sharma and Bhushan, 2019; Bhushan and Munshi, 2021) have reported higher accuracy rate for recognition of happiness, but this study confirms difference in terms of processing time as well.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…This is supported by the N400 effect observed in the ERF analysis and the absence of significant decoding latency in the MVPA analysis. Both the studies (Sharma and Bhushan, 2019; Bhushan and Munshi, 2021) have reported higher accuracy rate for recognition of happiness, but this study confirms difference in terms of processing time as well.…”
Section: Discussionsupporting
confidence: 79%
“…The findings clearly show neurophysiological evidence for hemispheric and hemifacial asymmetry in the processing of facial expressions of emotions. The other two studies using the same database presented only the findings of behavioral data (Sharma and Bhushan, 2019) or mix of the behavioral data and geometric analysis of these expressions (Bhushan and Munshi, 2021). Both of them could not examine hemispheric or hemifacial asymmetry, although they had a unique database with facial expressions captured from multiple angles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations